Waste Water Treatment Using a New Type of Coagulant. (2015) - Nutiu, Emil
Abstract: This paper presents the results of an experimental study on the design of a process and a plant design solutions for mechanical and chemical treatment. Benefits that shows the proposed process is about ensuring a much higher degree of purification of waste water pollutants than known solutions in terms of a low cost by using a new type of coagulant metal silicate. The raw material used to produce the coagulant is in the form of fine powder and was found in the composition of a sterile non-ferrous metallurgical slag. The process for achieving the coagulant-metal-silicates (CMS) is a waste water treatment coagulant prepared at sterile water treatment slag, technical sulfuric acid and water in proportions of gravity 1, 1-1, 1-9, 5, the dosage of coagulant to a pH of 4.3 ... 4.5, followed by adding milk of lime until a pH of 7.0 ... 7.5, homogenizing the mixture and the settling due to gravity, resulting in purified water chemical sludge. If the ferrous sulfate acts as we know, the coagulated material, with the addition of milk of lime, silicic acid acts as a flocculation accelerator. By combining the two effects to give a precipitate which settles easily, resulting in the highest part of the suspension and a higher adsorption of the organic pollutants. The presented method is considered as an alternative to conventional solutions using wastewater treatment from food processors industry.